Тransnational Project "Vox Mundi" - Experience with Implementing Movement as a Pedagogical Tool in Working with Children's Choirs - Јеlena D. Cvetković Crvenica; Milica B. Jovanović (University of Belgrade, Teacher Education Faculty, 2023)
Starting from the fact that from the onset of formal education students encounter choral singing as an activity successively linked to general music education, the paper emphasizes the importance of using movement as a pedagogocal tool for the development of immanent rhythm, vocal technique, and intonation in working with children's choirs. The main purpose of this research is to systematize the experience gained in the transnational project "Vox Mundi" carried out in Temisoara, Romania in 2022 in order to point to potential choices and future approaches to movement at choral rehearsals at general mucis education level. In the course of a ten-day intensive youth exchange, five multiplicative events, and the elaboration of three intellectual outcomes, a survey was conducted, with the sample including 50 elementary school choir singers, members of choral organizations of five partner countries (Romania, Serbia, Poland, France and Hungary). By reviewing and unifying the exercises from different choral music activites, we modeled an approach to specific general music education resources with the aim of acquiring the skills and competencies necessary for using movement with polyphonic singing. A significant level of advantages of integrating movement and singing was identified, while the correlation between the delibarate use of movement and an increased engagement was also identified as a factor that was consistently present. In addition, it was discovered that movement and music can illustrate emotional meaning of music and improve relationships among choral singers. This article focuses on practical suggestions which can provide new points for discussion on the necessity of using movement in working with members of children's choirs, children who are in the first or second cycle of elementary education.